2019
DOI: 10.1111/acel.12888
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxygenation revitalizes Alzheimer’s disease pathology through the upregulation of neurotrophic factors

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by Aβ‐induced pathology and progressive cognitive decline. The incidence of AD is growing globally, yet a prompt and effective remedy is not available. Aging is the greatest risk factor for AD. Brain aging proceeds with reduced vascularization, which can cause low oxygen (O2) availability. Accordingly, the question may be raised whether O2 availability in the brain affects AD pathology. We found that Tg‐APP/PS1 mice treated with 100% O2 at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 45 publications
1
74
0
Order By: Relevance
“…TrkB activation by BDNF in rat primary cortical culture produced a biphasic expression of Bdnf exon IV~IX mRNA, with the primary induction 1~3 h after TrkB stimulation and the delayed and protracted induction 24~72 hours after the stimulation, in which the early induction was much higher than the delayed induction [61], thus suggesting that the expression of Bdnf exon IV~IX mRNA occurs in a complex time course. TrkB-dependent BDNF expression is regulated by cAMP response element binding protein (CREB) [62] and Methyl-CpG binding protein 2 (MeCP2) [6364]. TrkB activation also increases TrkB expression via CREB activation [5965].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TrkB activation by BDNF in rat primary cortical culture produced a biphasic expression of Bdnf exon IV~IX mRNA, with the primary induction 1~3 h after TrkB stimulation and the delayed and protracted induction 24~72 hours after the stimulation, in which the early induction was much higher than the delayed induction [61], thus suggesting that the expression of Bdnf exon IV~IX mRNA occurs in a complex time course. TrkB-dependent BDNF expression is regulated by cAMP response element binding protein (CREB) [62] and Methyl-CpG binding protein 2 (MeCP2) [6364]. TrkB activation also increases TrkB expression via CREB activation [5965].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF expression is regulated by multiple factors, including CREB, MeCP2, and HDACs [6466]. Furthermore, genetic deficits of Mecp2 , Hdac1 , and Hdac2 in the dorsal striatum produced grooming behavior [67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MeCP2 siRNA treatment restored hippocampal dendritic spine numbers and memory deficits in a Morris water maze in amyloid-β-injected rats. However, amyloid-β was shown to reduce MeCP2 expression in immortalized hippocampal neurons and in the hippocampus of APP/PS1 mice [31], in contrast with the above finding. In addition, MeCP2 deficiency did not alter the level of APP in the cortex, although it disturbed the localization of APP to the cell membrane [50].…”
Section: Mecp2 and The Pathology Of Alzheimer Diseasementioning
confidence: 95%
“…Interestingly, a study revealed that hippocampal MeCP2 was upregulated in Alzheimer disease patients [30], but another study showed that MeCP2 expression was reduced in the hippocampus of APP/PS1 mice and that upregulation of hippocampal MeCP2 could play a therapeutic role in an Alzheimer disease mouse model [31]. These data demonstrate that there exists an interaction between Alzheimer disease and MeCP2, which requires an in-depth investigation.…”
Section: Methyl-cpg Binding Proteinmentioning
confidence: 99%
“…Zhao et al reported that resveratrol could significantly improve the impaired memory formation and synaptic plasticity in AD via downregulating the miR-124 level, which is accompanied with an increase of CREB and subsequently promoted BDNF synthesis [45], a key molecule in the neurobiological mechanisms relates to dendritic spine size and cognitive decline and also possesses neuroprotective properties against Aβ-induced neurotoxicity in cultured neurons and AD mouse models [105]. In addition, hyperoxygenation treatment has been found to revitalize AD pathology via increasing neurotrophic factors including BDNF [106]. However, miR-124 has been found to result in a significant downregulation of cocaine-induced plasticity by targeting and suppressing BDNF [107].…”
Section: Mechanisms Of Mir-124 In Alzheimer's Diseasementioning
confidence: 99%